A long-term perspective on the COVID-19: The bike sharing system resilience under the epidemic environment. (September 2022) - Bi, Hui; Ye, Zhirui; Zhang, Yuhan; Zhu, He
Abstract: Introduction: The sudden COVID-19 pandemic poses a fresh and tough challenge to bike sharing systems (BSS). With this epidemic as a shock event, this paper aspires to shed light on the phenomenon of changing demand and usage regularity in New York City's BSS under the epidemic environment, spanning a period of 18 months. Methods: Technically, BSS's normal performance and the timely responses to the outbreak could be conceptualized as having four different stages. One provides a comparative analysis of bike sharing spatial-temporal mobility patterns and connectivity of the bike sharing usage network, before and during the public health crisis with a macroscopic perspective. Also, a multivariate investigation of user and trip characteristics on BSS is conducted to uncover the difference in the frequency of outdoor and sojourn time between various user communities. Results: Due to the impact of the outbreak, BSS registered severe ridership drops, yet it quickly recovered to the pre-pandemic levels within months. The decline of bike sharing usage was felt throughout all the areas during the outbreak. However, there were places where BSS ridership actually increased, particularly in the areas near supermarkets, parks and hospitals. The less densely connected network of the bike sharing usage has also resulted in a reduction in users' destination heterogeneity. This study also finds evidence of the significant gender, age and cycling pattern gaps in response to potential risk. Conclusions: Investigating the dynamics of bike sharing usage will help to comprehend how the serious pandemic caused by COVID-19 impacts people's daily mobility. Practically, this work hopes to provide insights into adapting this unprecedented pandemic so as to respond to similar events in the future. Highlights: This study focuses on estimating the long-term impacts of the COVID-19 pandemic on bike sharing system. This study outlines the bike sharing usage variation at a spatial-temporal level in terms of intensity and network structure. This study uncovers the difference in the frequency of outdoor and sojourn time between various user communities. The study explores the role of a bike sharing program in a long-term epidemic environment.